Full‐field characterization of a fatigue crack: Crack closure revisited. Issue 10 (24th January 2018) - Tong, J.; Alshammrei, S.; Wigger, T.; Lupton, C.; Yates, J.R.
Abstract: The full‐field of a fatigue crack, ahead and behind the crack tip, has been examined in this work using Digital Image Correlation. We measured, in situ, the surface crack opening displacements at selected locations behind the crack tip and the evolution of the near‐tip displacements and strains ahead of the crack tip, during loading and unloading in a model material of a standard compact tension specimen. In addition, the stress intensity factor for the compact tension specimen was also estimated from the Williams' series expansion by using the displacements obtained from Digital Image Correlation as a function of applied load. The results present a complete picture of the crack tip field at the selected load levels, where events both ahead and behind of the crack tip were studied for the first time in crack driving and attenuation effects. We hope that the results provide some fundamental insights into the full‐field behaviour of a crack tip under cyclic loading conditions and shed light on the phenomenon of crack closure and its relevance to fatigue crack driving force Δ K under small‐scale yielding conditions.